The Impact of Performance Appraisal System on Organizational Climate (Case Study -Gaza Electricity Distribution Company –2022) - Wasim Swidan; Kalsom Ali; Ali Nasser Ali Al-Tahitah (Emirates College for Educational and Psychological Sciences, 2024)
Non-Indexed Publication